Changes in cost of locomotion are higher after endurance cycling than running when matched for intensity and duration - Sabater-Pastor, F.; Faricier, R.; Metra, M.; Murias, J. M.; Brownstein, C. G.; Millet, G. (Medicine & Science in Sports & Exercise, 2023)
Introduction Cost of locomotion (CL) has been shown to increase after endurance running and cycling bouts. The main purpose of this study was to compare, in the same participants, the effect of both modalities on CL when matched for relative intensity and duration.